Alcoholysis of Starch to Produce Alkyl Polyglycosides with Sub‐Critical Isooctyl Alcohol. Issue 4 (5th May 2016) - Zou, Mihua; Chen, Jinyang; Wang, Yingdi; Li, Mingli; Zhang, Chao; Yang, Xuanyu
Abstract: Alkyl polyglycosides are a type of green non‐ionic surfactants, and are synthesized from starch and isooctyl alcohol with a new eco‐friendly one‐step sub‐critical alcoholysis with the temperature ranging from 240 to 320 °C and autogenous pressure. Yellow alkyl polyglycosides were obtained through the oxidative decoloration of alcoholysis products at a temperature 80 °C for 2 h with a 5 % weight content of hydrogen peroxide. The alkyl polyglycoside product was determined to be isooctyl glucoside with HPLC, IR and NMR. The CMC and HLB of the produced isooctyl glucoside were 2.5 g/L and 17, respectively. With the weight ratio of isooctyl alcohol to starch at 10, a temperature of 260 °C and a reaction time of 2 h, the yield of isooctyl glucoside can attain 132.21 % versus a theoretical yield (defined as the final mass of isooctyl glycoside/initial mass of starch) of 183 %.